Economic analysis on the relationship between medical cost, obesity, health outcomes and labour market in Malaysia - Foo, Lee Peng (2017)
Obesity has reached epidemic levels worldwide, including Malaysia. Although the government of Malaysia had introduced various programs to reverse the obesity epidemic, there is no significant change in outcome. In fact, obesity prevalence remains high and even shows dramatic increase although many efforts have been done. Thus, this study takes a critical look at the economic cost of obesity via direct cost and indirect cost. The study intends to (a) identify the relationship between Body Mass Index (BMI) and personal medical cost, (b) examine the burden of obesity via the Disability-Adjusted Life Year (DALY); (c) examine obesity and its effect on labour market performance. For the first objective, Generalized Linear Models (GLMs) is utilized on patient level data obtain from Serdang Hospital in year 2011. The second objective, the mortality data was obtained from Department of Statistics; while prevalence and incidence data were extracted from existing literature and computed by DISMOD II. DISMOD II is a software tool introduced by the World Health Organization to check the consistency of estimates of incidence, prevalence, duration and case fatality for diseases. Lastly, for the third objective, an ordinal regression is performed by using the data retrieved from self-administered questionnaire. A total of 531 candidates who aged 20 to 59 years old responds to the questionnaires via face-to-face interviews and online questionnaire. After carefully selection, only 391 respondents were including in the analysis. The findings from the first objective suggest obese patients paid lower personal medical cost as they are covered mainly by the public hospital policies and government subsidies. The policy was aimed to improve the welfare of the citizen in overall health status, but it is fair to say that it has wrongly promoting obesity related diseases (or urban diseases due to lifestyle choices) which makes the obese patients pay lower personal medical cost. As for the second objective, population attribution fraction and disability-adjusted life year were applied to quantify years of life lost from premature death and number of years lost due to disability resulting from obesity. PAF is the proportional reduction in population disease or mortality if the population were entirely unexposed compare to the present exposure pattern. The burden of disease attributable to obesity was 2951 PYs and 1657 PYs per 1000 person for men and women respectively. Among all obesity related diseases worldwide, hypertension has the most significant burden of disease attributable to being obese, where men were 523 PYs per 1000 persons; this was followed by women 524 PYs per 1000 persons. On the other hand, the result from third objective suggests that employers do not consider workers appearance in their hiring process. The key success to employment is primary depending on education level and age (assuming age increases substantially with experiences). However, the obese workers admitted that they received unfavorable treatment during the employment. Thus, this study would like to propose further research in using questionnaires to distinguish between private and public servants, which will help to eliminate the sticky effect on their salaries. The outcome of this study is crucial as it gives comprehensive information on the consequences of obesity to the overall economic. The information from this study also enables the authorities to develop activities and programs to combat obesity and to maintain healthy lifestyle among Malaysians.